Adsorption behavior of lead on aquatic sediments contaminated with cerium dioxide nanoparticles. (December 2016) - Wang, Chao; Fan, Xiulei; Wang, Peifang; Hou, Jun; Ao, Yanhui; Miao, Lingzhan
Abstract: Aquatic sediments serve as an important sink for engineered nanomaterials (ENMs), such as metal oxide nanoparticles (MeO NPs) and carbon nanotubes (CNTs). Owing to their remarkable properties, ENMs demonstrate significant potential to disturb the adsorption behavior of other contaminants in aquatic sediments, thereby altering the bioavailability and toxicity of these contaminants. Thus far, most studies have investigated the effect of CNTs on the adsorption of other contaminants on sediments. Cerium dioxide nanoparticles (CeO2 NPs), as one of the important MeO NPs, are also inevitably discharged into aquatic sediments because of their widespread use. In this study, we investigated the adsorption behavior of Pb 2+ on sediments spiked with CeO2 NPs at a weight ratio of 5.0%. The results showed that the adsorption rates at three stages occurring during adsorption clearly increase for sediments contaminated with CeO2 NPs. Moreover, the results obtained from the adsorption isotherms indicated that the Langmuir isotherm model best fits the isotherm data for both sediments and those contaminated with CeO2 NPs. After spiking the sediments with CeO2 NPs, the theoretical maximum monolayer adsorption capacity ( Q max ) for Pb 2+ increased from 4.433 to 4.995 mg/g and the Langmuir isotherm coefficient ( K L ) decreased from 8.813 to 7.730 L/g. The effects of CeO2 NPs on the surface charge and pore surface properties of sediments were also studied as these properties affect the adsorption of several chemicals in sediments. The results showed that pHzpc, SBET, Sext, and average pore size of sediments clearly decrease for sediments contaminated with CeO2 NPs. Hence, the strong adsorption capacity of CeO2 NPs and the changes of sediment surface charge and pore surface properties caused by CeO2 NPs are important factors affecting the adsorption behavior of Pb 2+ . The potential risk of Pb 2+ in aquatic environment may increase with CeO2 NPs buried in sediments. Highlights: Pb 2+ adsorption behavior in CeO2 NPs contaminated aquatic sediments was investigated. The pHzpc and pore surface properties of sediments changed much for CeO2 NPs contamination. The adsorption rate and maximum adsorption capacity of Pb 2+ increased for CeO2 NP-contaminated sediments. The adsorption affinity between Pb 2+ and sediments decreased for CeO2 NP-contaminated sediments. Abstract : CeO2 NPs contamination increased the Pb 2+ maximum adsorption capacity and decreased the adsorption affinity between Pb 2+ and sediments.